Characteristics of complaints and functional outcomes of conservatively treated clavicle fractures in Dr. Soetomo general hospital: A case series - Brilliant Citra Wirashada; Maghrizal Roychan; Teddy Heri Wardhana (Universitas Muhammadiyah Surabaya, 2021)
ABSTRACT Shoulder pain is a major complaint of patients with clavicle fractures as a result of trauma. At present most clavicle fracture treatments are performed surgery, although conservative therapy can produce the same results. This report aimed to show whether there were complaints of shoulder pain or disability in patients who have suffered clavicle fractures treated conservatively. There were fifteen patients with clavicle fractures at Dr. Soetomo Surabaya from January to July 2015, consisting of 14 male and one female patient. Data was taken from medical records, patient clinical records, home visits, physical examinations, SPADI questionnaires, and Quick DASH for patients. The results of SPADI questionnaire were varied; there were eight patients (53%) with an output of 0%, one patient (7%) each with a score of 0.63%, 1.25%, 5.90%, 7.13%, 8.50%, 9.90%, and a score of 10.50%. The results of calculating the Quick DASH questionnaire score also varied. There were ten patients (67%) with a score of 0, three patients (20%) with a score of 2.27, one patient (7%) with a score of 13.6, and one patient (6%) with a score of 6.81. In conclusion: (1) From the evaluation of 15 patients, there were no complaints of pain and disability in the shoulder joint. (2) From the evaluation of the results of the calculation of the SPADI questionnaire and Quick DASH, there were no significant complaints of shoulder joint pain and disability. (3) The conservative treatment of closed fractures on the clavicle can still be a reliable choice of treatment. Keywords : Clavicle fractures, shoulder pain, conservative clavicle.Correspondence to: brijurnalqanun@gmail.com